Pengaruh pengelolaan agroekosistem terhadap kelimpahan kutu loncat jeruk Diaphorina citri Kuwayama (Hemiptera: Liviidae) - M. Zuhran; Gatot Mudjiono; Retno Dyah Puspitarini (Perhimpunan Entomologi Indonesia, 2021)
Asian citrus psyllid (ACP) Diaphorina citri Kuwayama is a serious problem in citrus because it transmits huanglongbing (HLB) disease. Agricultural practices without paying attention to the agroecosystem complexity often cause the agroecosystem more suitable for insect pests proliferation and less friendly to natural enemies. The research aims to study the effectiveness of agroecosystem management compared to conventional farming in the ACP control. The effects of both treatments on the diversity and abundance of ACP’s natural enemies as well as the incidence and severity of HLB were also studied. Agroecosystem management consists of preventive and responsive actions. Preventive action was carried out through a polyculture system, planting refugia and legume cover crop, providing beetle banks, applying lime, applying organic and inorganic fertilizers, citrus pruning intensively, maintaining drainage ditches, and mechanical weed control. Responsive action is short-term control when the abundance of ACP reaches the action threshold. Responsive action was carried out through biological or chemical control. Meanwhile, conventional farming is a series of conventional farming and pest control techniques commonly applied by farmers. Each treatment was applied in three orchards of Siam Orange cv. Pontianak Citrus nobilis Lour var. microcarpa Hassk. The results showed that agroecosystem management was more effective in controlling the ACP population so that its abundance was lower and less fluctuated than conventional farming. ACP’s natural enemies in agroecosystem management were also more diverse than conventional farming. The abundance of ACP’s natural enemies and the incidence and severity of HLB in the two treatments were not significantly different.